Michelle

answers: 1

Register to add an answer

The time for answering the question is over

200 cents

Answer:

3(2p - 1) = 5 - (3p - 2)

By opening the brackets, we get

6p - 3 = 5 - 3p - 2

By transposition method, we get

6p + 3p = 5 - 2 + 3

By simplifying the like terms, we get

9p = 6

or, p = 6/9

or, __p____ ____=____ ____2____/____3__

The value of p is 2/3 .

197

Stefan

For answers need to register.

Contacts

mail@expertinstudy.com

Feedback

Expert in study

About us

For new users

For new experts

Terms and Conditions